2020
DOI: 10.1016/j.ygyno.2019.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Second-line lenvatinib in patients with recurrent endometrial cancer

Abstract: Objective. This study assessed the efficacy of lenvatinib, a multitargeted tyrosine kinase inhibitor, as secondline therapy in patients with unresectable endometrial cancer. The primary end point was the objective response rate (ORR) as assessed by independent radiologic review (IRR). Secondary end points included median progression-free survival (PFS), overall survival (OS), and clinical benefit rate. Exploratory end points examined the association of baseline levels of plasma biomarkers (50 circulating cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 30 publications
0
34
0
2
Order By: Relevance
“…8 12-16 Lenvatinib monotherapy was also evaluated in a phase 2 trial of 133 patients with recurrent endometrial cancer with an objective response rate of 14.3% with a manageable safety profile. 17 Clinical trials evaluating pembrolizumab plus lenvatinib in patients with endometrial cancer demonstrated objective response rates of 32-40%. 10 11 Results were similar among patients with mismatch repair-proficient tumors (30-36%).…”
Section: Discussionmentioning
confidence: 99%
“…8 12-16 Lenvatinib monotherapy was also evaluated in a phase 2 trial of 133 patients with recurrent endometrial cancer with an objective response rate of 14.3% with a manageable safety profile. 17 Clinical trials evaluating pembrolizumab plus lenvatinib in patients with endometrial cancer demonstrated objective response rates of 32-40%. 10 11 Results were similar among patients with mismatch repair-proficient tumors (30-36%).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of EC patients with multitarget tyrosine kinase inhibitors sorafenib, sunitinib, nintedanib and lenvatinib achieved disappointing results [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] ( Table 5 ).…”
Section: Antiangiogenic Agentsmentioning
confidence: 99%
“…Interestingly, lenvatinib has been previously reported to have a potential anti-tumor activity in recurrent or metastatic EC [ 39 , 40 ]. Growing evidence indicates that dysregulation of the FGFR signaling pathway is involved in human tumorigenesis [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%